(untitled) (Asian Journal of Pharmaceutics (AJP), 2023)
Since a few years ago, the delivery of drugs through the skin has gained popularity. By doing so, it gets around problems with the oral route. Despite the fact that only a few pathways are as appealing as the transdermal route, it is difficult to deliver drugs through the skin. Researchers have developed a technique that allows the medicine to be encapsulated into vesicles, which may then go deep into the layer of skin to reach the target spot. Consequently, bioactive agents can penetrate the skin more effectively. Liposomes, niosomes, transethosomes, and transferosomes are vesicular systems that frequently remain collected in the skin layers. Transethosomes can pass through multiple layers of skin because they have tiny particle sizes and can change the form of vesicles more easily than another vesicular system. Transethosomes allow the medicine to be conveniently delivered to the target place. Ethanol, phospholipids, and an edge stimulator make up transethosomes. Transethosomes’ ability to penetrate the skin is improved by ethanol and edge stimulators. It increases patient cooperation because it is a non-intrusive procedure. It also improves the effectiveness of drug entrapment. These vesicles can hold a wide range of medications, including pain relievers, antitumor medicines, steroids, proteins, and peptides.